Oilseed flax cultivation: optimizing phosphorus use for enhanced growth and soil health - He, Ning; Huang, Fang; Luo, Dingyu; Liu, Zhiwei; Han, Mingming; Zhao, Zhigang; Sun, Xian (Frontiers in Plant Science, 2024)
Introduction Oilseed flax (Linum usitatissimum L.) yields are phosphate (P) fertilizer-limited, especially in the temperate semiarid dryland regions of North China. However, there are limited studies on the effects of P-fertilizer inputs on plant growth and soil microorganisms in flax planting systems. Methods To address this gap, a field experiment was conducted with four treatments: no P addition and application of 40, 80, and 120 kg P ha-¹, respectively. The aim was to investigate the influence of various P fertilizer inputs on yield, plant dry matter, P use efficiency, as well as the population of soil arbuscular mycorrhizal fungi (AMF) and bacteria in dryland oilseed flax. Results Our results show that the P addition increased the dry matter, and the yield of oilseed increased by 200% at 120 kg P ha-1 addition with inhibition on the growth of AMF hyphae. The moderate P supply (80 kg ha-1) was adequate for promoting P translocation, P use efficiency, and P recovery efficiency. Soil pH, available P, and available K significantly (p< 0.05) promoted the abundance of the dominant taxa (Acidobacteria_GP6, Sphingobacteria and Bacteroidetes). In addition, it is imperative to comprehend the mechanism of interaction between phosphorus-fertilizer inputs and microbiota in oilseed flax soil. Discussion This necessitates further research to quantify and optimize the moderate phosphorus supply, regulate soil microbes to ensure high phosphorus utilization, and ultimately establish a sustainable system for oilseed flax cultivation in the local area.